Chapter 9 Marking the Face, Curing the Soul? Reading the Disfigurement of Women in the Later Middle Ages - Kukita Yoshikawa, Naoë (Boydell & Brewer, 2015)
Current preoccupations with the body have led to a growing interest in the intersections between religion, literature and the history of medicine, and, more specifically, how they converge within a given culture. This collection of essays explores the ways in which aspects of medieval culture were predicated upon an interaction between medical and religious discourses, particularly those inflected by contemporary gendered ideologies. The essays interrogate this convergence broadly in a number of different ways: textually, conceptually, historically, socially and culturally. They argue for an inextricable relationship between the physical and spiritual in accounts of health, illness and disability, and demonstrate how medical, religious and gender discourses were integrated in medieval culture. Naoë Kukita Yoshikawa is Professor of English in the Faculty of Humanities and Social Sciences at Shizuoka University. Contributors: Louise M. Bishop, Elma Brenner, Joy Hawkins, Roberta Magnani, Takami Matsuda, Liz Herbert McAvoy, Irina Metzler, Denis Renevey, Patricia Skinner, Juliette Vuille, Diane Watt, Naoë Kukita Yoshikawa.